Avaliação do tempo de trânsito colônico em portadores de constipação intestinal crônica: estudo comparativo de dois métodos utilizando marcadores radiopacos - Marisa Fonseca Magalhaes (2006)
Constipation is one of the most prevalent conditions in clinical gastroenterology accounting for one of the most common chronic digestive complaints and an estimated 2.5 million doctor visits per year in the USA. In the majority of the cases constipation is a condition determined for many factors and the results from therapeutics approaches are often unsatisfactory. For refractory constipation when patients do not get improvement with the osmotic laxatives or dietetics recommendations and there is not any secondary cause, functional testsare indicated. Colonic transit time, defecography, manometry have all been reported to assist in the evaluation of constipated patients. They should indicate more specific treatment depending of the cause of constipation. Two different techniques for measuring colonic transit time were tested in thirty-one constipated patients and ten controls without constipation. The results for control group were: maximum total colonic transit time was 68 hours, medium 31.6±20.77 hours; 6.4±6.1 hoursfor transit time into right colon, 5.6 ± 5.5 hours for left colon and 20.6±19.9 hours into rectosigmoide for Metcalfs method. For Hintons method we found only two radiopaque markers on the fifth day. Among constipated patients the colonic transit time was increased in seventy percent:medium of 133.33 ±23.05hours for total colonic transit time, 33.23±21.95 hours for right colon transit, 9.61±23.48 hours for left colon transit and 22.2±19.12 hours for rectosigmoid transit. The results were not different when we considered age, time of evolution for constipation or frequency of evacuation among constipated patients. There was no differencefor rectosigmoid transit time in patients with evacuatory effort. The results for Metcalfs and Hintons methods were concordant in 100 % for controlsand the accuracy for Hintons was 76%, considering Metcalf s technique as gold standard. In conclusion we found colonic transit time increased in 68% of constipated patients and the most frequent pattern was increased transit time into left colon, colonic inertia pattern was found in 19% and outlet delay was not observed at all. The Hintons method was very useful for control group with normal colonic transit time and may be used as initial approach for constipated patients.